2017
DOI: 10.3390/ijerph14050482
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Rotavirus Genogroup A and Norovirus Genogroup II in Bassaseachic Falls National Park Surface Waters in Chihuahua, Mexico

Abstract: In areas lacking potable water treatment, drinking contaminated water may represent a public health threat. In addition to enteropathogenic bacteria and parasites, fecal contamination in water environments is associated with the transmission of enteric viruses and other causal agents of infectious disease. Rotavirus and norovirus are the main enteric viral agents responsible for diarrheic outbreaks. The aim of the present study was to detect seasonal variation of rotavirus and norovirus in the surface water at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
3
0
3
Order By: Relevance
“…For synthesizing cDNA for Reverse Transcription (RT) amplification, 300 ng of the extracted-purified total RNA sample was used for was performed with, using Moloney Murine Leukemia Virus Reverse Transcriptase (MMLV RT) (Promega, Madison, WI), following the manufacturer's instructions (11). For the PCR assay, 200 ng of the extractedpurified sample was amplified using previously reported primers (Table 1).…”
Section: Rt-pcr and Pcrmentioning
confidence: 99%
“…For synthesizing cDNA for Reverse Transcription (RT) amplification, 300 ng of the extracted-purified total RNA sample was used for was performed with, using Moloney Murine Leukemia Virus Reverse Transcriptase (MMLV RT) (Promega, Madison, WI), following the manufacturer's instructions (11). For the PCR assay, 200 ng of the extractedpurified sample was amplified using previously reported primers (Table 1).…”
Section: Rt-pcr and Pcrmentioning
confidence: 99%
“…Su kaynaklı enfeksiyonlarda norovirüs yaygın olarak bildirilmektedir. Doğası gereği, bu kontaminasyon sıklıkla biyolojik atıklarla ilişkilidir [4]. Çevre koşullarında uzun süre yaşama şansı olduğu için bu Norovirüslerin önemini arttırmaktadır [9].…”
Section: Tartışma Ve Sonuçunclassified
“…Çevre koşullarında uzun süre yaşama şansı olduğu için bu Norovirüslerin önemini arttırmaktadır [9]. Yenilenme yeteneği hızlı olan ve farklı pek çok genogrup, genotip ve varyantları bulunan norovirüslerin moleküler epidemiyolojik olarak sularda incelenerek durumunun bilinmesi, hem epidemiyolojik veri sunması, hem de ulusal aşı çalışmalarında da kullanılabilmesi açısından değerlidir [4].…”
Section: Tartışma Ve Sonuçunclassified
“…In Mexico, previous studies revealed the presence of enteric viruses including NoVs and HAdVs in superficial freshwater affected by human faecal pollution in urban and rural settings (Mazari‐Hiriart et al ; Arredondo‐Hernández et al ; Delgado‐Gardea et al ). In coastal areas of Mexico, the presence of NoV GII was reported from an estuarine environment located in the most productive shrimp cultivation area in the state of Sinaloa (Hernández‐Morga et al ), and in marine recreational waters in the same state (León‐Félix et al ).…”
Section: Introductionmentioning
confidence: 99%